Improving Measures of Handwashing Behavior - Ram, Pavani K.; Luby, Stephen P.; Halder, Amal Krishna; Islam, M. Sirajul; Granger, Stewart (World Bank, Washington, DC, 2014)
Handwashing (HW) efficacy studies have taken the form of randomized controlled trials and the outcome(s) of interest have primarily been health related. That is, the intervention group, which received HW promotion, and the control group have been compared according to disease burden. As HW promotion is scaled up and adopted by organizations of varying research capacity, evaluation techniques that are more field-friendly, inexpensive, and readily adaptable are required. Data on HW behavior may be observed, inferred, or reported. Observed data may be considered the most objective type of data available for measuring HW behavior. Observations may be conducted using spot checks or continuous observation. Continuous structured observation is frequently used to evaluate HW behavior as well as other hygiene behaviors. This technique consists of the placement of a trained observer in a target family's home for several key hours in the day. The observer can conduct continuous observation of opportunities for hygiene behaviors and track whether or not hygiene behaviors are practiced at those opportunities. Observers can also track the quality of observed hygiene behaviors, for example the use of soap or ash for washing hands.